Effect of coolant temperature and circulation flowrate on the performance of a vertical finned crystallizer - Amran, N. A. (Elsevier Ltd, 2016)
Performance of a newly developed freeze concentrator named vertical finned crystallizer (VFC) in concentrating glucose solution was evaluated. The VFC was designed as an attempt to provide an efficient progressive freeze concentration (PFC) system by providing larger heat transfer area for crystallization. Glucose solution at an initial concentration of 11°Brix was concentrated through the new PFC system. The performance of the crystallizer was analysed in parallel with the effect of coolant temperature and circulation flowrate to the system efficiency, represented by effective partition constant (K) and solute recovery (Y). The results show that the efficiency of the system has significantly improved portrayed by the lowest K value obtained of 0.383 and the highest Y value obtained of 0.96 g glucose/g initial glucose at intermediate coolant temperature and higher circulation flowrate. Thus, the VFC is evidently proven to have a high potential to be integrated in a PFC process as an efficient concentration system. The results obtained offer some guidelines on how to produce an efficient PFC system through parameter setting.